Effects of coagulants on the catalytic properties of iron–manganese co-oxide filter films for ammonium and manganese removal from surface water. (1st January 2020) - Cheng, Ya; Zhang, Shasha; Huang, Tinglin; Cheng, Lijie; Yao, Xuan
Abstract: The removal of ammonium (NH4 + ) and manganese (Mn 2+ ) is an important issue when treating surface water for drinking. A pilot-scale experiment was carried out with two parallel filter columns (filters R1 and R2) to compare the effects of three different coagulants (ferric chloride (FeCl3 ), polymerization ferric chloride (PFC), and polymeric aluminum ferric chloride (PAFC)) on the catalytic oxidation of an iron–manganese (Fe–Mn) co-oxide filter film for NH4 + and Mn 2+ removal from surface water. In the results, FeCl3 was not conducive to the removal of NH4 + and Mn 2+, probably because of the decrease in pH after its hydrolysis. PFC had a negligible effect on the catalytic activity of the Fe–Mn co-oxide for NH4 + and Mn 2+ removal. With PAFC, the NH4 + removal efficiency of filter R2 began to decrease after 50 days, but the catalytic activity of the Fe–Mn co-oxide for Mn 2+ removal remained unchanged. In order to explore the influence mechanisms of different coagulants, numerous analytical techniques were used to characterize the physicochemical properties of the Fe–Mn co-oxide samples. The results indicated that the difference in bonding interactions between aluminum (Al) and the Fe–Mn co-oxide with different running times may have caused the difference in activity. The bonded Al fraction was found to be tough to remove by backwashing in filter R2 with PAFC. The change in state of Al bonded to the surface might have been the fundamental cause of the decreased catalytic activity of the Fe–Mn co-oxide. Based on its removal performance over time, PFC coagulant can effectively ensure the continuous catalytic removal of NH4 + and Mn 2+ from surface water with the Fe–Mn co-oxide filter. Highlights: Pilot-scale experiment to evaluate catalytic oxidation of Fe–Mn co-oxide filters. Effects of three different coagulants (FeCl3, PFC, and PAFC) were evaluated. Filter morphology, structure, and composition during operation were considered. PFC is the most suitable coagulant for NH4 + and Mn 2+ removal from surface water.